Do Corporations Invest Enough in Environmental Responsibility? - Kim, Yongtae; Statman, Meir (2012)
Proponents of corporate environmental responsibility argue that corporations shortchange shareholders by investing too little in environmental responsibility. They claim that corporations can improve their financial performance by increasing their investment in environmental responsibility. Opponents of corporate social responsibility argue that corporations shortchange shareholders by investing too much in environmental responsibility. They claim that corporations can improve their financial performance by reducing their investment in environmental responsibility. Yet, others claim that corporations serve their shareholders well by investing just enough in social responsibility, not too little and not too much. If so, corporations increase their investment in environmental responsibility when an increase improves financial performance and reduce their investment in environmental responsibility when a decrease improves financial performance. Our evidence is consistent with this last claim. We find that the behavior of corporations is consistent with the claim that they act in the interest of shareholders, increasing or decreasing their investment in environmental responsibility as necessary to improve their financial performance.
Keywords: Corporate Social Responsibility; Causality; Corporate financial performance; Corporate environmental responsibility